Analysis of Errors in Solving Geometry Problems Reviewed from Written Mathematical Communication Skills of Teacher Candidates - Radiusman, Radiusman; Simanjuntak, Maslina (Universitas Islam Negeri Raden Intan Lampung, 2021)
This descriptive qualitative research aims to analyze the mistakes of primary school teacher candidates in solving geometry problems reviewed from mathematical written communication skills. This research was conducted on 37 students who were in the 2nd semester and took 3 people as research subjects with the criteria of moderate written communication skills. Data collection techniques were carried out using tests and interviews. The written mathematical communication test was given in the form of a description where each question contains one written mathematical communication indicator. The results of this study indicated that the mistakes were: low knowledge of prerequisite concepts, lack of student experience in working on problems, weak imagination in connecting statements, and low ability to perform calculations.